Preparação e caracterização de carvão ativado magnético obtido a partir da serragem de madeira sapelli (Entandrophragma cylindricum) para adsorção do corante azul brilhante - Nascimento, Victoria Ximenes (2023)
The contamination of water bodies by dyes has been a problem to be fought because the large amounts of effluents released into water bodies are harmful to the environment and living beings. Thus, it is necessary to develop and improve technologies that promote the efficient treatment of effluents. In this context, in the present study, two magnetic activated carbons were prepared from Sapelli wood sawdust, using single-step pyrolysis with KOH and NiCl2 as activation and magnetization agents. In the preparation, the proportion of biomass, KOH and NiCl2 was 1:1:0.5 and 1:1:1, therefore, the carbons were named MAC1105 and MAC111, respectively, according to the proportion used. The coals were characterized and applied as adsorbents to remove the brilliant blue dye. The characterization was performed using different techniques such as MEV/EDS, FTIR, BET, TGA, XRD, VSM and pHPCZ. According to the characterization, mesoporous materials with ferromagnetic properties and the presence of nanostructured Ni particles were obtained. The MACs showed the potential to be reused in 4 cycles of adsorption and showed high efficiency (up to 90% removal) in the treatment of a simulated effluent. CAM111 showed a higher surface area (331.543 m2 g -1 ), faster kinetics (around 10 min) and a higher adsorption capacity. The adsorption capacity was around 40 mg g -1 for MAC1105 and 96 mg g-1 for MAC111. Thus, MAC111 was selected, and adsorption experiments were carried out from the kinetic, equilibrium and thermodynamic points of view. In the adsorption experiments, the adsorbent dosage was 0.75 g L-1 and the pH of the solution was 4.0. Furthermore, kinetic and equilibrium data were adequately represented by pseudo-second order (PSO) and Sips models, respectively. The maximum adsorption capacity was 111.50 mg g-1 at 55 °C. The thermodynamic study revealed that the adsorption was a spontaneous, favorable and endothermic process. Furthermore, mechanistic elucidation suggested that electrostatic interactions, hydrogen bonding, π–π and n–π interactions were involved in the adsorption of brilliant blue dye on MAC 111.